Family history of diabetes moderates metabolic depression endophenotypes in overweight/obese adults. (July 2022) - Ong, Stacie L.; Abbasi, Fahim; Watson, Kathleen; Robakis, Thalia; Myoraku, Alison; Rasgon, Natalie
Abstract: Objective: Insulin resistance (IR) is linked to depressive disorders, and there is growing evidence that targeting IR may be beneficial in treating them. We examine the association between depressive symptoms and a direct measure of IR, and whether family history of type 2 diabetes (FHx-T2DM) or major depressive disorder (FHx-MDD) moderate this relationship. Methods: Cross-sectional data were collected from 96 primarily overweight/obese adults ages 25–50 without diabetes or clinical depression. Multiple regression and correlation analyses were used to assess the association between depressive symptoms and a direct measure of IR (steady-state plasma glucose) as well as moderating effects of FHx-T2DM or FHx-MDD. Results: In the total sample, elevated depressive symptoms were positively associated with IR (p = 0.005). IR was associated with depressive symptoms in subjects with FHx-T2DM (p = 0.002) or FHx-MDD (p = 0.009) whereas BMI was associated with depressive symptoms in subjects without FHx-T2DM (p = 0.049) or FHx-MDD (p = 0.029). The odds of being in the top tertile of IR increased with elevated depressive symptoms alone (OR, 4.22; 95%CI, 1.15 to 17.33), presence of FHx-T2DM alone (OR, 3.42; 95%CI, 1.26 to 10.00), and presence of both FHx-T2DM and elevated depressive symptoms (OR, 10.08; 95%CI, 1.94 to 96.96). Conclusions: Our findings indicate that depressive symptoms are positively associated with a direct measure of IR in overweight/obese individuals without diabetes or clinical depression. This association is moderated by FHx-T2DM. Early identification of groups vulnerable to IR related to depressive symptomatology may be useful for determining personalized interventions that have the potential to reduce morbidity in later years. Highlights: Depressive symptoms were positively associated with a direct measure of insulin resistance in overweight/obese individuals without diabetes or clinical depression. This association was moderated by family history of type 2 diabetes. Subjects with family history of type 2 diabetes had increased odds of being in the top tertile of insulin resistance when they exhibited depressive symptoms.